The effect of gluten-free diet on mean platelet volume, neutrophil and neutrophil/lymphocyte ratio in children with celiac disease (Annals of Medical Research, 2021)
Aim: Celiac Disease (CD) is a chronic, autoimmune and systemic disease. In the present study, the purpose was to investigate the effect of a gluten-free diet on Mean-Platelet-Volume (MPV), neutrophil and neutrophil/lymphocyte Ratio (NLR).Material and Methods: A total of 106 patients who were diagnosed with CD and who were followed-up by the Pediatric Gastroenterology Clinic of the Hospital, and 50 healthy children were included in the study. The demographic data of the patients and the neutrophil, lymphocyte, platelet, NLR were recorded before the diagnosis and one-year after gluten-free diet. The hematologic parameters of the patients were compared with the healthy control group at the diagnosis time. Following a one-year gluten-free diet, the hematologic parameters of the patients were compared with the parameters at the diagnosis time.Results: The mean age of the patients was 12.1±3.2 years (7-16 years), and the mean age of the control group was 14.5±4.1 years (12-16 years). A total of 48% (51/106) of the patients were female and 34% (17/50) of the control group was female. Hematological parameters of patients compared pre-dietary and post-dietary; lymphocyte and platelet ratios were significantly higher, whereas neutrophils, MPV and NLR were significantly lower. Neutropenia was detected in 15 patients before the diet. It was observed that neutrophil level reached the normal range after gluten-free diet in patients with neutropenia.Conclusions: The MPV, neutrophil and NLR values, that was low during the diagnosis, may be ameliorative with the gluten-free diet. In addition, CD should be considered in the differential diagnosis of neutropenic patients.
Keywords: Celiac Disease; MPV; NLR; PLR